At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's solve the system of equations step by step:
[tex]\[ \begin{cases} 3x - 2y = 5 \\ 2x + 4y = 14 \end{cases} \][/tex]
### Step 1: Solve one equation for one of the variables
Let's solve the first equation for \( x \):
[tex]\[ 3x - 2y = 5 \][/tex]
Add \( 2y \) to both sides:
[tex]\[ 3x = 5 + 2y \][/tex]
Divide both sides by 3:
[tex]\[ x = \frac{5 + 2y}{3} \][/tex]
### Step 2: Substitute into the other equation
Substitute \( x = \frac{5 + 2y}{3} \) into the second equation \( 2x + 4y = 14 \):
[tex]\[ 2\left(\frac{5 + 2y}{3}\right) + 4y = 14 \][/tex]
Multiply through by 3 to clear the fraction:
[tex]\[ 2(5 + 2y) + 12y = 42 \][/tex]
Distribute \( 2 \):
[tex]\[ 10 + 4y + 12y = 42 \][/tex]
Combine like terms:
[tex]\[ 10 + 16y = 42 \][/tex]
Subtract 10 from both sides:
[tex]\[ 16y = 32 \][/tex]
Divide by 16:
[tex]\[ y = 2 \][/tex]
### Step 3: Substitute back to find \( x \)
Substitute \( y = 2 \) back into the equation \( x = \frac{5 + 2y}{3} \):
[tex]\[ x = \frac{5 + 2(2)}{3} \][/tex]
Simplify:
[tex]\[ x = \frac{5 + 4}{3} = \frac{9}{3} = 3 \][/tex]
### Final Solution
The solution to the system of equations is:
[tex]\[ x = 3, \quad y = 2 \][/tex]
Therefore, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations are [tex]\( x = 3 \)[/tex] and [tex]\( y = 2 \)[/tex].
[tex]\[ \begin{cases} 3x - 2y = 5 \\ 2x + 4y = 14 \end{cases} \][/tex]
### Step 1: Solve one equation for one of the variables
Let's solve the first equation for \( x \):
[tex]\[ 3x - 2y = 5 \][/tex]
Add \( 2y \) to both sides:
[tex]\[ 3x = 5 + 2y \][/tex]
Divide both sides by 3:
[tex]\[ x = \frac{5 + 2y}{3} \][/tex]
### Step 2: Substitute into the other equation
Substitute \( x = \frac{5 + 2y}{3} \) into the second equation \( 2x + 4y = 14 \):
[tex]\[ 2\left(\frac{5 + 2y}{3}\right) + 4y = 14 \][/tex]
Multiply through by 3 to clear the fraction:
[tex]\[ 2(5 + 2y) + 12y = 42 \][/tex]
Distribute \( 2 \):
[tex]\[ 10 + 4y + 12y = 42 \][/tex]
Combine like terms:
[tex]\[ 10 + 16y = 42 \][/tex]
Subtract 10 from both sides:
[tex]\[ 16y = 32 \][/tex]
Divide by 16:
[tex]\[ y = 2 \][/tex]
### Step 3: Substitute back to find \( x \)
Substitute \( y = 2 \) back into the equation \( x = \frac{5 + 2y}{3} \):
[tex]\[ x = \frac{5 + 2(2)}{3} \][/tex]
Simplify:
[tex]\[ x = \frac{5 + 4}{3} = \frac{9}{3} = 3 \][/tex]
### Final Solution
The solution to the system of equations is:
[tex]\[ x = 3, \quad y = 2 \][/tex]
Therefore, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations are [tex]\( x = 3 \)[/tex] and [tex]\( y = 2 \)[/tex].
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.